Does Teacher Education Matter? Comparison of Education and Science Major Teachers' Assessment Literacy - (:unkn) unknown (ANI PUBLISHING, 2021)
The purpose of this study was to investigate science teachers' assessment literacy having different majors (education versus science) and compare those teachers' assessment literacy. A multiple-case study, one of the qualitative research designs, was utilized to fulfill the aim. Four science teachers, two from each major, who were teaching at public schools during the 2017-2018 semesters, participated in the study. Pre-interviews, observations, post-interviews, and documents were used as data collection tools during the investigation. Content analysis was conducted using science teachers' assessment literacy model that exists in the literature. The findings of the study revealed that science teachers were similar and different from each other with respect to several dimensions of assessment literacy, which are views about learning, assessment purposes, assessment strategies, what to assess, and assessment interpretation. Recommendations for science education research and implications for science teacher education are provided.
Keywords: Science education; in-service science teachers; assessment literacy; case study; FORMATIVE ASSESSMENT; CONCEPTIONS; KNOWLEDGE